2022
DOI: 10.3390/molecules27207015
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of the Polycyclic Aromatic Hydrocarbon and Elemental Profile of Smoked Fish

Abstract: Fish are vulnerable to environmental pollutants such as polycyclic aromatic hydrocarbon and heavy metals. As one of the most commonly applied processing methods, the smoking of different species has been applied globally. Hence, this study aims to investigate the smoking process on the polycyclic aromatic hydrocarbon and elemental accumulation of the five different species (rainbow trout, Atlantic bonito, horse mackerel, sea bass, and Atlantic bluefin tuna) which are commonly processed and traded in the smoked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 62 publications
0
5
1
Order By: Relevance
“…Other authors have also observed a decrease in the protein content of smoked rainbow trout. Tümerkan [37] found a protein content of 23.7% in hot smoked rainbow trout, corresponding to 3.79% nitrogen content, a slightly higher value than that obtained in this study. Duman and Kuzgun [38] determined that smoked rainbow trout nuggets had a higher content of crude protein and total lipids than fresh nuggets.…”
Section: Physico-chemical Parameterscontrasting
confidence: 75%
“…Other authors have also observed a decrease in the protein content of smoked rainbow trout. Tümerkan [37] found a protein content of 23.7% in hot smoked rainbow trout, corresponding to 3.79% nitrogen content, a slightly higher value than that obtained in this study. Duman and Kuzgun [38] determined that smoked rainbow trout nuggets had a higher content of crude protein and total lipids than fresh nuggets.…”
Section: Physico-chemical Parameterscontrasting
confidence: 75%
“…In a comparative study, the authors found that PAH levels in smoked fish could be attributed to the differences in fat and moisture contents, as they were higher in smoked mackerel than in sardine, cigar minnows or tuna [ 40 ]. Other studies, not necessarily on fish meat, demonstrated that the fat content and membrane of the smoked product had a major influence on PAH contamination [ 25 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, there are two sources of PAHs in fish meat: bioaccumulation ia environmental sources [ 15 ] and contamination via food processing methods. Most PAHs in fish meat are generated directly during heat treatments such as roasting [ 16 , 17 ], barbequing [ 18 , 19 ], grilling [ 20 , 21 ], frying [ 22 , 23 ] and smoking [ 24 , 25 ]. Numerous comparative studies have concluded that smoked fish contains the highest amounts of PAHs [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it is essential to ensure the quality and safety of fish during processing while retaining the maximum quality of the original attributes, such as texture, flavor, and taste (Fomena Temgoua et al, 2022). Fisheries products (live, fresh, or frozen) account for 45% of global market consumption, while preserved products (dried, salted, brined, fermented, or smoked) account for 12% (Ekonomou et al, 2020;Gomes et al, 2021;Aksun Tümerkan, 2022). A significant increase in the production of rainbow trout (Oncorhynchus mykiss) has been realized, as this species has been widely cultured worldwide (Vásquez et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Smoking is an ancient food processing method that extends the shelf life of food by reducing moisture content and the antioxidant effects of phenols to minimize the microbial load (Iko Afé et al, 2021). It also improves sensory characteristics, including flavor, aroma, and appearance (Aksun Tümerkan, 2022;Praveen Kumar et al, 2022). The convenience of smoked fish products sold as ready-to-eat food has become popular (Bolívar et al, 2021).…”
Section: Introductionmentioning
confidence: 99%